Soviet-type Nationalization in East Central Europe - Veress, Emőd (Lectures on East Central European Legal History, 2023)
Following the Second World War, a significant transformation occurred in private law under the Soviet type dictatorial regime. Suppression – akin to abolition – of private property, wide-scale nationalization, and collectivization are presented in this chapter through the legal norms by which the socialist transfiguration of the national economy was meant to be achieved. The chapter presents the general East Central European trends and, to provide specific details, uses Romanian and Hungarian historical and legal evolutions as a case study.KEYWORDS: civil law, communism, state property, nationalization, collectivization, East Central Europe,Hungary, Romania.